Tandem Repeat Polymorphisms Genetic Plasticity, Neural Diversity and Disease - Hannan, Anthony J.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2012)
This book addresses the role of tandem repeat polymorphisms (TRPs) in genetic plasticity, evolution, development, biological processes, neural diversity, brain function, dysfunction and disease. There are hundreds of thousands of unique tandem repeats in the human genome and their polymorphic distributions have the potential to greatly influence functional diversity and disease susceptibility. Recent discoveries in this expanding field are critically reviewed and discussed in a range of subsequent chapters, with a focus on the role of TRPs and their various gene products in evolution, development, diverse molecular and cellular processes, brain function and disease.
Tandem Repeat Polymorphisms: Mediators of Genetic Plasticity, Modulators of Biological Diversity and Dynamic Sources of Disease Susceptibility -- Evolution of Simple Sequence Repeats as Mutable Sites -- Single Amino Acid and Trinucleotide Repeats: Function and Evolution -- Promoter Microsatellites as Modulators of Human Gene Expression -- Dynamic Mutations: Where Are They Now -- Unstable Mutations in the FMR1 Gene and the Phenotypes -- Molecular Pathways to Polyglutamine Aggregation -- Polyglutamine Aggregation in Huntington and Related Diseases -- Selective Neurodegeneration, Neuropathology and Symptom Profiles in Huntington$1 (Bs Disease -- Kennedy$1 (Bs Disease: Clinical Significance of Tandem Repeat s in the Androgen Receptor -- Characterising the Neuropathology and Neurobehavioural Phenotype in Friedreich Ataxia: A Systematic Review -- Polyalanine Tract Disorders and Neurocognitive Phenotypes.s
Keywords: Medicine; Medical genetics; Neurosciences; Biomedicine; Biomedicine general; Neurosciences; Gene Function; Electronic books